2004
DOI: 10.1520/jfs2004019
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol (Ultram®) Concentrations in Death Investigation and Impaired Driving Cases and Their Significance

Abstract: We reviewed a series of 66 deaths in Washington State between 1995–2000 in which tramadol (Ultram® and Ultracet®, Ortho-McNeil) was detected in the decedent's blood, in order to assess the role tramadol was determined to have played. Additionally, we reviewed a series of 83 impaired driving cases in which tramadol was detected in order to establish a non-lethal blood tramadol concentration reference range. In both populations, tramadol was consistently found together with other analgesic, muscle relaxant, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 11 publications
4
29
0
Order By: Relevance
“…According to our knowledge previous studies have not investigated the presence or absence of intention among the cases of tramadol intoxications. A comparable forensic US study concluded that despite increased detection of tramadol in forensic investigations, no corresponding increase occurred in the number of deaths solely attributable to tramadol [16]. This has been confirmed by the FDA [21] and the manufacturer Johnson & Johnson [11].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…According to our knowledge previous studies have not investigated the presence or absence of intention among the cases of tramadol intoxications. A comparable forensic US study concluded that despite increased detection of tramadol in forensic investigations, no corresponding increase occurred in the number of deaths solely attributable to tramadol [16]. This has been confirmed by the FDA [21] and the manufacturer Johnson & Johnson [11].…”
Section: Discussionmentioning
confidence: 85%
“…Using forensic materials, Clarkson et al [16] reported that tramadol might be a significant contributor to lethal intoxication when taken in excess with other drugs that depress central nervous functions, such as analgesics, muscle relaxants and antidepressants.…”
Section: Introductionmentioning
confidence: 99%
“…A frozen vial of the patient's blood was then sent to a specialized laboratory for assessment of tramadol and O-demethyl-tramadol (the main metabolite), which yielded blood concentrations of 26.1 mg/dL of tramadol (largely exceeding the serum therapeutic ranhe of 0.28-0.61 mg/dL) and 5.3 mg/dL of O-demethyltramadol, respectively. 19 Interestingly, it was lately found that the patient had obtained the tramadol bottles by another jailed man, who was using the drug for chronic post-traumatic pain.…”
Section: Case Reportmentioning
confidence: 99%
“…These have shown that tramadol may induce physical dependence and withdrawal reactions, and is implicated in misuse, abuse and diversion (143), as well as intoxications, emergency department visits (185), and drug-related deaths (186,187). Yet, the addictive properties of tramadol are considered to be low (188)(189)(190). Notably, due to other drugrelated problems including some adverse reactions the benefit-risk profile of tramadol at the effective dose is a matter of debate (191).…”
Section: Tramadolmentioning
confidence: 99%